Arabidopsis Lectin EULS3 Is Involved in ABA Signaling in Roots - Dubiel, Malgorzata; Beeckman, Tom; Smagghe, Guy; Van Damme, Els J. M. (Frontiers in Plant Science, 2020)
The Arabidopsis thaliana lectin ArathEULS3 is upregulated in particular stress conditions and upon abscisic acid (ABA) treatment. ABA is a plant hormone important for plant growth and stress responses. During stress ABA is perceived by PYR/PYL/RCAR receptors, inhibiting protein phosphatases PP2C thereby enabling SNRK2 kinases to start downstream phosphorylation cascades and signaling. PYL9, one of the ABA receptors was identified as an interacting partner for ArathEULS3. Promoter::GUS activity studies revealed the expression of ArathEULS3 in the central root cylinder and the cells flanking young lateral root primordia, and showed enhanced expression in root tips after ABA treatment. Transcript levels for ArathEULS3 increased after exposure to ABA and osmotic treatments. ArathEULS3 CRISPR KO mutants served as a tool to expand the knowledge on the role of ArathEULS3 in plant development. KO lines revealed a longer root system compared to WT plants, and showed reduced sensitivity to ABA, salt and osmotic conditions. Additionally it was noted that the KO mutants had more emerged lateral roots when grown in high osmotic conditions. Together these data suggest that ArathEULS3 may be an important player in ABA responses in roots.